Black-Brown Coalition and the Fight for Economic Justice, 1960-1974 - Jones, William P. (Labour / Le Travail, 2014)
This article reviews the book, "Black-Brown Coalition and the Fight for Economic Justice, 1960-1974," by Gordon K. Mantler.